2010
DOI: 10.1007/s00198-010-1472-2
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in the ALOX12 gene and osteoporosis

Abstract: Our study suggests that genetic variants in ALOX12 may influence BMD and fracture risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 40 publications
0
19
0
Order By: Relevance
“…Osteoporosis is caused by a bone remodeling disturbance in which bone resorption exceeds bone formation [16]. Whereas trabecular bone is severely affected already after few years (around 6) in AN patients, in postmenopausal women a similar break-down occurs over a longer time span (around 25 years).…”
Section: Discussionmentioning
confidence: 99%
“…Osteoporosis is caused by a bone remodeling disturbance in which bone resorption exceeds bone formation [16]. Whereas trabecular bone is severely affected already after few years (around 6) in AN patients, in postmenopausal women a similar break-down occurs over a longer time span (around 25 years).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, our results should be interpreted cautiously, and further studies should be conducted to determine the strength of these associations in various populations. However, our previous study [33] found no association between rs312470 or the other four SNPs from ALOX12 and peak BMD in Chinese nuclear families with male offspring. This finding raised the possibility of a sexspecific association of ALOX12 with the BMD [12,34].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Pratico et al [40] suggested that the ALOX12 levels and activity in the frontal and temporal regions of brains exhibiting Alzheimer's disease are significantly increased. Our previous study [33] found a significant association between the rs2073438 SNP in the ALOX12 gene and the total fat mass (TFM) and total lean mass (TLM) in a QTDT study of Chinese nuclear family with male offspring, suggesting this SNP's involvement in the variation of the obesity phenotype, perhaps through a PPARγ-dependent pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The rationale for SNP selection at the time when genotyping was performed is outlined below. SNPs for ALOX12 were selected from the literature as having been previously investigated for BMD [16,18,20]. SNP rs312466…”
Section: Genotypingmentioning
confidence: 99%
“…is located in the promoter, while rs1126667 and rs2292350 are NCBI tagging SNPs located in an LD block [16]. For ALOX15, with the exception of rs8074545 upstream of the coding region (which is intergenic and therefore has potential functionality) all selected SNPs were tagging SNPs previously investigated for BMD (rs748694; rs9894225; rs916055; rs2619112) [20].…”
Section: Genotypingmentioning
confidence: 99%